Leveraging 1-wire communication bus system for secure home automation (2017)
Home automation is a rising technology that is available to anyone thanks to the reduce cost of the embedded systems. Since the appearance of different products to create your own domotic system, and the recent popularity around the Internet of Things (IoT) technology, the domotics industry has changed. The ability to control devices through the Internet creates numerous vulnerabilities to the system, allowing an attacker to control or see everything. In this work, we present a domotic system which uses a leveraged 1-wire as its communication channel. The original system lacks of any kind of security. Our objective is to implement information security through the encryption of the system’s commands, so we can assure the CIA triad (Confidentiality, Integrity and Availability). The results show that we achieve a secure communication without affecting the user experience due to the low overhead our approach provides. © Springer International Publishing AG 2017.